Cognitive remediation therapy for patients with anorexia nervosa: preliminary findings - Tchanturia, Kate (BioMed Central, 2007)
BACKGROUND: Anorexia nervosa (AN) is a severe mental illness. Drug treatments are not effective and there is no established first choice psychological treatment for adults with AN. Neuropsychological studies have shown that patients with AN have difficulties in cognitive flexibility: these laboratory based findings have been used to develop a clinical intervention based on Cognitive Remediation Therapy (CRT) which aims to use cognitive exercises to strengthen thinking skills. AIMS: 1) To conduct a preliminary investigation of CRT in patients with AN 2) to explore whether cognitive training improves performance in set shifting tasks 3) to explore whether CRT exercises are appropriate and acceptable to AN patients 4) to use the data to improve a CRT module for AN patients. METHODS: Intervention was comprised of ten 45 minute sessions of CRT. Four patients with AN were assessed before and after the ten sessions using five set shifting tests and clinical assessments. At the end, each patient wrote a letter providing feedback on the intervention. RESULTS: Post intervention, three of the five set shifting assessments showed a moderate to large effect size in performance and two showed a large effect size in performance, both indicative of improved flexibility. Patients were aware of an improvement in their cognitive flexibility qualitative feedback was generally positive towards CRT. DISCUSSION: This preliminary study suggests that CRT changed performance on flexibility tasks and may be beneficial for acute, treatment resistant patients with AN. Feedback gathered from this small case series has enabled modification of the intervention for a future larger study, for example, by linking exercises with real life behavioural tasks and including exercises that encourage global thinking. CONCLUSION: This exploratory study has produced encouraging data supporting the use of CRT in patients with AN: it has also provided insight into how the module should be tailored to maximise its effectiveness for people with acute AN.